Improving the Military Vocational Training of Cadets at Military Institute - Yu. G. Bychenko; T. M. Balandina (Высшее образование в России, 2019)
Military institutions are traditionally focused on the implementation of the classical, narrow form of educational development of professional knowledge and skills of cadets. In modern conditions, a transition is taking place to a broad system of professional development that determines the formation of a wide range of professional potential of future officers, the development of not only narrow professional knowledge and skills, but also potential abilities for active creativity, motivation for systematic collection, processing and use of new informational data. To study the factors of inhibition of the educational process in the modern military institute, the results of the sociological research “Social and Labor Development in the Assessments of Cadets of the Saratov Military Institute” are analyzed. This analysis shows that military vocational training is characterized by informational isolation, rigid administrative organizational educational culture. The latter leads to a discrepancy between the formally stated and necessary, as well as the actually emerging creative potential of cadets (graduates) of Russia’s military institutions. The military institute lacks free access to Internet resources, a significant part of the information flow of the external social environment. Administrative technologies of interaction between the teacher and the students prevail, there are no favorable conditions for creative self-realization, complex development of creative projects, self-development of the intellectual potential of cadets, the practice of including cadets in the system of tactical management and self-management, organizing their own leisure time is limited. In this regard, changes are necessary in two directions: 1) providing organizational and informational conditions and opportunities for the creative implementation of students, as well as stimulating creative educational, scientific, and self-governing leisure activities of cadets; 2) the formation of organizational structures that purposefully support and organize innovative, managerial and selfgoverning activities of cadets. It is necessary to form innovative values of the educational process, the creative interaction of students with teachers. It is important to focus the educational and scientific-educational process on the processing and formation of new knowledge, on the activation of the innovative potential of cadets, that is, on the development of abilities to implement innovations that ensure a qualitative increase in the effectiveness of the military-professional activity of actors.